Acupressure and Health Education in Reducing Dysmenorrhea Pain: Akupresur dan Edukasi Kesehatan dalam Mengurangi Nyeri Dismenore - Nabilah Fatya Tsabita; Siti Cholifah; Yanik Purwanti; SM Faridah Hanum (Indonesian Journal on Health Science and Medicine, 2026)
General Background: Dysmenorrhea is a common reproductive health issue among adolescents that can interfere with daily activities and learning processes. Specific Background: Various non-pharmacological interventions, including acupressure and health education, have been explored as alternative approaches to manage menstrual pain among young women. Knowledge Gap: However, limited studies integrate both educational media and acupressure techniques as a combined approach to improve knowledge and reduce pain simultaneously. Aims: This study aims to examine the application of health education and acupressure techniques in addressing dysmenorrhea among adolescents. Results: The findings indicate that the intervention contributes to improved understanding of dysmenorrhea management and supports the reduction of pain intensity through non-pharmacological methods. Novelty: The study highlights a combined approach using educational media and acupressure practice as an integrated intervention model. Implications: These findings provide practical insights for implementing accessible and low-risk interventions in adolescent reproductive health programs, particularly in educational settings. The study also supports the development of preventive strategies through health promotion and self-care practices. Keywords: Dysmenorrhea, Acupressure, Health Education, Adolescents, Non Pharmacological Therapy Key Findings Highlights Combined intervention improves understanding of menstrual pain management Non-drug technique supports reduction of discomfort intensity Educational media strengthens self-care awareness among adolescents